Ectopic expression of Populus MYB10 promotes secondary cell wall thickening and inhibits anthocyanin accumulation - Jiang, Peng-Fei (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.